(untitled) (Third Sector Social Economic Review, 2025)
The aim of this study is to determine the impact that women’s cooperatives have on local economic development. In this context, a field study was conducted with women’s cooperatives located in Erzurum. With the approval issued on 29.12.2022 under Decision No. 13 by the Erzurum Technical University Scientific Research and Publication Ethics Committee, a survey was conducted with 173 women who are members of these cooperatives. In the study, an exploratory factor analysis was performed on statements regarding the role of women’s cooperatives in local economic development, and eight factors were identified. These factors were named as follows: economic and social life, local production, local products, regional investments, women’s employment, household income, women’s socialization, and women’s personal development. Additionally, a Mann-Whitney U Test was conducted to determine whether participants’ attitudes toward the eight factors obtained through exploratory factor analysis differed significantly based on the location, type, and years of experience of the women’s cooperatives. As a result, it was found that participants’ attitudes toward local economic development factors did not show a statistically significant difference based on the location and type of the cooperative. However, according to the cooperative’s years of experience, the impact of women’s cooperatives on women’s socialization, local investments, women’s employment, household income, women’s personal development and local production showed a statistically significant difference at the 5% level.